Perceived Stress, Contributing Factors and Coping Mechanisms in Prospective Medical Students of Karachi: An Exploratory Study (Medical Forum Monthly, 2024)
Objectives: To determine the perceived level of stress, identify the factors contributing to it and the coping mechanisms among Medical College Admission Test (MCAT) candidates.Study Design: Cross sectional exploratory studyPlace and Duration of Study: This study was conducted at Anees Hussain (to provide MCAT preparation) all branches of amajor private MCAT preparation center in Karachi immediately before the scheduled test date in July 2016 to November 2016.Materials and Methods: All candidates registered for MCAT preparation at the center were requested to participate in the study. Perceived stress was measured using Cohen’s Perceived Stress Scale (PSS-14). A separate structured questionnaire was used to determine contributing factors on a 3 point Likert scale and coping mechanisms on a dichotomous scale. Data was analyzed using SPSS 21.0.Results: A total n=500 respondents completed the study. There were 24.0% (n=120) males and 76.0% (n=380) females with mean age 18±0.75 years. Majority 81.4% (n= 407) had premedical education from Sindh Board. The overall mean PSS-14 score was 30.00 ±7.31 and 48% candidates had a score greater than mean. Preference for public sector institute was cited by 80.3% (n=305) females and 78.2% (n=93) males whereas financial constraints was consideration for this preference among 45.9% (n= 174) females as compared to 30.8% (n=36) males. Major factors contributing to stress were self-study problem, examination pressure, vast syllabus, time shortage and high level of competition. Pressure to study medicine against will was admitted by 19.0% (n=72) females and 12.5% (n=15) males. The most frequent coping mechanism in both males and females were sleeping and talking to someone. Conclusion: There is a moderate to high level of stress present in prospective medical students of Karachi. Students entering medical college with prior stress may be at added risk with consequent impacts on learning and physical health. Standardized premedical education at national level and a universal admission test can reduce stress levels. Good study management skills should be inculcated since school to prevent stress of competitive examinations. Medical undergraduate education is extensive and potentially stressful. Therefore, medical colleges should initiate stress management counseling to incoming students immediately after commencement.